Influence of hydrogen implantation and oxidation on air on the structure and mechanical properties of nickel based coating PG-19-01 - Kadyrzhanov, K.K.; Kislitsin, S.B.; Komarov, F.F.; Pogrebnjak, A.D.; Rusakov, V.S.; Tuleushev, Y.Zh. (Науковий фізико-технологічний центр МОН та НАН України, 2008)
Influence of oxidation on air and hydrogen implantation on the structure and mechanical properties of nickel based coating PG-19N-01 deposited on iron and stainless steel C0.12Cr18Ni10Ti substrate and also of iron with plasma treatment of surface were studied. It is shown, that implantation by protons with energy from 0.6 to 1.6 MeV up to doze 3•10^18 proton/cm^2 lead to insignificant changes of structure and strength properties of PG-19N-01 coating. In the samples oxidized on air at temperatures 500 °С, 700 °С and 900 °С during three hours increase in microhardness and strength of the material at mechanical tests on static bend is observed. Вивчено вплив окислювання на повітрі й імплантації водню на структуру й механічні властивості нікелевих покриттів PG-19N-01, нанесених на залізну підкладинку та з нержавіючої сталі 30.12Cr18Ni10Ti підкдадинки, а також заліза із плазмовою обробкою поверхні. Показано, що імплантація протонами з енергією від 0,6 до 1,6 МеВ з дозою 3•10^18 протон/см^2 приводить до незначних змін структури й міцності характеристик покриття PG-19N-01. У зразках, окислених на повітрі при температурах 500 °С, 700 °С и 900 °С у плині 3-х годин спостерігалося збільшення мікротвердості й зміцнення матеріалу при механічних випробуваннях на статичний вигин. Изучено влияние окисления на воздухе и имплантации водорода на структуру и механические свойства никелевых покрытий PG-19N-01, нанесенных на железную подложку и из нержавеющей стали С0.12Cr18Ni10Ti подложки, а также железа с плазменной обработкой поверхности. Показано, что имплантация протонами с энергией от 0,6 до 1,6 МэВ с дозой 3•10^18 протон/см^2 приводит к незначительным изменениям структуры и прочностных характеристик покрытия PG-19N-01. В образцах, окисленных на воздухе при температурах 500 °С, 700 °С и 900 °С в течении 3-х часов наблюдалось увеличение микротвердости и упрочнения материала при механических испытаниях на статический изгиб.